Eğik Eğilme Ve Eksenel Kuvvet Etkisindeki Genel Kesitlerin Analizi İçin Bir Algoritma - Güngör, Abdulkadir (Fen Bilimleri Enstitüsü, 2015)
Betonarme, çelik veya kompozit kesitleri geometrik şeklinden bağımsız, doğrusal ve doğrusal olmayan malzeme davranışı altında, belirli bir normal kuvvet etkisinde iki eksenli moment hesabı yapan bir algoritma önerilmiştir. Algoritma iteratif bir matris hesap modeli üzerine kurulmuştur.

Developed algorithm is able to regardless of the form of the cross section geometry, linear and nonlinear material behavior under biaxial under a certain normal force gives the opportunity to do analysis. It is based on the matrix expression. Limited and ultimate strain can be calculated. There is an iterative computational model of the software.
Ultimate Strain Analysis Of Concrete, Reinforced And Composite Sections Biaxial Bending Developing Algorithms That Can Perform
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2015
Keywords: Betonarme Kesitler; Çelik Kolonlar; Beton Kolonlar; Kompozit Kesitler; Reinforced Concrete Sections; Steel Columns; Concrete Columns; Composite Sections